The Determinants Factors of Customer Loyalty with Customer Satisfaction as the Mediating Role: A Case Study of J&T Express Service in JABODETABEK - Havidz, Ikramina Larasati Hazrati; Rahmansyah, Nizar; Wiratih, Hernawati W. Retno; Havidz, Hazimi Bimaruci Hazrati (Jurnal Logistik Indonesia, 2022)
The rapid growth of technology, has an impact on logistics services. The need for logistics services has also increased many times along with the increasing number of consumers who shop online. Logistics services play a central role in the e-commerce business. Therefore, the study has purpose to determine the customer loyalty of a particular logistic service at Indonesia. The customer of J&T Express reside around JABODETABEK was taken as the study objective. SmartPLS was the analytical tools used to analyzed the primary data. The study found that Service Quality and customer satisfaction signified a positive and significant relationship on the customer loyalty. Customer satisfaction is determined by Service Quality. Customer satisfaction is signified under the study to possessed a partial mediating role in determining the Service Quality on the customer loyalty.